PROBLEMATIKA PESERTA DIDIK DAERAH TERPENCIL DI ERA REVOLUSI DIGITAL DAN SOLUSINYA MENURUT PERSPEKTIF AGAMA ISLAM - Cholifah Cholifah; Abdul Muhid (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
This article explains how the problems of students living in remote areas live with many obstacles in this era of the digital revolution. The education gap between rural and urban areas can be observed based on schools in urban areas that have adequate facilities and also have competent teachers. In this era of digital revolution, various problems arise which are the impact of the progress of the times, especially in the field of education. The method used in this study is literature review where this method is carried out by collecting information related to remote area students in the era of the digital revolution through various journals and books. The information that has been obtained is then analyzed and drawn into a conclusion. This article also discusses how to solve the various problems faced by students in remote areas in the era of the digital revolution from the Islamic perspective, including: Students who are in remote areas to always try to update their knowledge and insights despite various circumstances and conditions. obstacles must be overcome (QS. Ar-Ra'd (13): 11) and all Muslims everywhere are required to be individuals who are able to master and excel in science and even technology as a means in a better life for the happiness of the world until the hereafter (QS. Al-Isra (17): 36).